2016
DOI: 10.1080/14786419.2016.1163692
|View full text |Cite|
|
Sign up to set email alerts
|

Biological activities, phenolic profiles and essential oil components of Tanacetum cilicicum (BOISS.) GRIERSON

Abstract: Tanacetum species are consumed as tea in Turkey. We comparatively evaluated the phytochemical potentials and antioxidant activities of the essential oil and methanolic extracts of Tanacetum cilicicum. The chemical constitutes of T. cilicicum essential oil and antioxidant activity of this species was analysed by gas chromatography-mass spectrometry (GC-MS) method. Bicyclo (3,1,1) hept-2-en-4-ol (21.92%), camphor (15.56%) and 1,8-cineole (13.45%) which are oxygenated monoterpenes were found as the major constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Also, TCCEA possessed the highest FRAP activity with 42.02 mg trolox/g extract while TCCH had the lowest FRAP activity with 7.175 mg trolox/g extract. Gecibesler et al (2016) reported that total phenolic amount of methanol extracts obtained from different parts of T. cilicicum were found ranging from 99.53±2.39 to 268.02±0.97 mg GAE/g extract. They found that phenolic contents for the methanol extract of flower of T. cilicicum were higher than leaf and stem of T. cilicicum [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, TCCEA possessed the highest FRAP activity with 42.02 mg trolox/g extract while TCCH had the lowest FRAP activity with 7.175 mg trolox/g extract. Gecibesler et al (2016) reported that total phenolic amount of methanol extracts obtained from different parts of T. cilicicum were found ranging from 99.53±2.39 to 268.02±0.97 mg GAE/g extract. They found that phenolic contents for the methanol extract of flower of T. cilicicum were higher than leaf and stem of T. cilicicum [16].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest phenolic amount was found in hexane extract of flower of T. cilicicum (6.106 mg GAE/g). Gecibesler et al (2016) reported that total flavonoid amounts of methanol extracts obtained from different parts of T. cilicicum varied from 26.76 ± 3.53 to 86.41 ± 1.62 mg QE/g of the extract. It was found that the flavonoid content of the flower parts (26.76 ± 3.53 mg QE/g extract) was the lowest followed by stem (29.59 ± 2.58 mg QE/g extract).…”
Section: Discussionmentioning
confidence: 99%
“…argenteum, and T. argenteum subsp. canum [22] and T. alyssifolium [23], and T. cilicicum [24] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Though Michel et al (2020) indicated that kaempherol glycosides are the main phenolic in the Asteracea, but present study showed that the major phenolic compound of T. densum taxa is catechin. Similarly, Gecibesler et al (2016) found that catechin was a principal component of Tanacetum. The other phenolics studied were in low amounts or absent (Table 4).…”
Section: Resultsmentioning
confidence: 90%